N2 injection to enhance coal seam gas drainage (N2-ECGD): Insights from underground field trial investigation. (15th January 2022) - Yang, Xin; Wang, Gongda; Du, Feng; Jin, Longzhe; Gong, Haoran
Abstract: Pre-gas drainage plays a significant role of preventing gas disasters in underground coal mines. However, it is difficult to reduce the gas content to below the threshold values, especially in low permeability coal seams in China. Previous field trials on the enhanced coalbed methane recovery (ECBM) by nitrogen injection mostly focused on the ground. Until now, few attempts on N2 injection to enhance coal seam gas drainage (N2 -ECGD) and no sufficient evidences can indicate the good effect. In this study, exploratory tests of N2 -ECGD were carried out in underground low-gas coal seams (with gas content less than 5 m 3 /t). An experiment to displace the CH4 in coal by N2 injection under constant pressure conditions was first carried out. The results show that continuous N2 injection can promote the desorption of CH4 in the coal pores, which cannot be achieved under normal pressure. N2 -ECGD field trials were conducted in the working face of a coal mine in Hejin City, Shanxi Province, China. The effective pressure of N2 injection (EPI) was investigated. Intermittent and continuous N2 injection trials were carried out to study the response characteristics of the gas flow rate, CH4 concentration, and flow rate. The results show an EPI of 0.45 MPa and gas injection radius of 5 m. The gas flow rate increased significantly after N2 injection. Although the CH4 concentration decreased, the CH4 flow rate remained high. On the basis of the change characteristics of gas drainage parameters, the physical process of N2 -ECGD was analyzed. The research results obtained in this study can serve as a reference for the application of N2 -ECGD in low permeability coal seams. The study also provides a new technical approach for local gas prevention and control in underground coal mines. Highlights: Laboratory experiments on CH4 single diffusion and N2 injection to displace CH4 were carried out. N2 -ECGD field trials were conducted on an underground coal seam with a gas content of less than 5.0 m 3 /t. The effective pressure of N2 injection in the trial coal seam was determined. The physical process of N2 -ECGD was analyzed.